Real time virtual simulation of an underactuated pendulum-driven capsule system - Keattikorn Samarnggoon (2018)
In this paper, a real time virtual simulation framework which is the foundation for studying human adaptive mechatronics (HAM) is proposed. This framework allows researchers to interact and experiment with the system in real time. Thus, motion control patterns can be identified and learned with, for example, a heuristic strategy. The prototype is developed with an underactuated pendulum-driven capsule robot model. Motion control patterns are identified and presented. The experimentation results demonstrate the proposed concept. © 2012 IEEE.